Indoloquinolines: Possible Biogenesis from Common Indole Precursors and their Synthesis using Domino Strategies - T. Parvatkar, Prakash; S. Parameswaran, Perunninakulath (Current Organic Synthesis, 2016)
The tetracyclic indoloquinoline alkaloids, cryptolepine, neocryptolepine, isocryptolepine and their analogues, isolated from the West African shrub Cryptolepis sanguinolenta are known to display promising antimalarial, antibacterial, antiviral, antihyperglycemic and cytotoxic properties. Biogenesis of these different linear and angular indoloquinolines are most probably through the reaction of anthranilic acid with selected indole derivatives – indoxyl, oxindole, 3-formyl indole, etc., all by-products during tryptophan biosynthesis from chorismate. As part of our ongoing screening program of bioactive compounds, several of these natural products and their derivatives, including few halogenated metabolites were synthesized in our laboratory using simplified domino approaches. Apart from codifying their probable biosynthetic pathways, this article also summarizes our synthetic studies, most of which were planned mimicking the natural biosynthetic pathways.
Keywords: Cryptolepis sanguinolenta